Evaluation of the Findings of Patients Who Underwent Sutureless Flanged Transconjunctival Intrascleral Intraocular Lens Implantation with or without Pars Plana Vitrectomy. (2nd September 2021) - Suren, Elcin; Kalayci, Mustafa; Cetinkaya, Ersan; Kucuk, Mehmet Fatih; Dogan, Mehmet Erkan; Durmaz, Doğan; Duman, Fulya; Erol, Muhammet Kazim
Abstract : Purpose . To compare the visual outcomes and complications of patients who underwent flanged transconjunctival sutureless intrascleral intraocular lens (SIS IOL) implantation after anterior and pars plana vitrectomy. Methods . All patients who underwent flanged transconjunctival SIS IOL fixation using a 27-gauge needle between September 2017 and November 2019 and were followed up for at least six months were evaluated. The cases in which anterior vitrectomy was performed were classified as Group 1, and those that underwent pars plana vitrectomy were classified as Group 2. The best-corrected visual acuity (BCVA), spherical equivalent values, corneal endothelial cell density, and intraocular pressures were compared between the two groups before and after the operation. Intraoperative and postoperative complications were assessed. Results . The study included 108 eyes of 108 patients who were included in the study. Group 1 consisted of 48 patients and Group 2 comprised of 60 patients. When the findings between Groups 1 and 2 were compared in the postoperative period, there was no statistically significant difference in terms of the mean intraocular pressure increase, endothelial cell density, BCVA, and spherical equivalent value (P = 0.818, 0.601, 0.368, and 0.675, respectively). When all the patients were considered as a single group, the mean spherical value at the sixth postoperative month was 0.3 ± 2.2 D (min-max, (−5.5)–(+6)), the mean cylindrical value was −1.7 ± 2.4 D (min-max, (−9.25)–(+4)), and the mean spherical equivalent value was −0.5 ± 2.3 D (min-max, (−6.5)–(+6)). Conclusion . The flanged transconjunctival SIS IOL fixation technique performed using a 27-gauge needle is safe and effective in the patient group with aphakia and lens/IOL dislocation or subluxation. However, in patients planned to undergo flanged transconjunctival SIS IOL implantation, pars plana vitrectomy seems to be a more suitable option than anterior vitrectomy to reduce complications.